Lagomorphs pikas, rabbits, and hares of the world - Smith, Andrew T., 1946- (Johns Hopkins University Press, 2018)
"Numbering 92 species worldwide, the order Lagomorpha is a focal point of conservation efforts. Approximately one-quarter of all lagomorphs are under conservation concern, and a few are quite literally on the brink of extinction. Here, leading conservation biologist Andrew T. Smith and his colleagues bring together the world's lagomorph experts in the most comprehensive reference on the order ever produced. With detailed species accounts--illustrated with stunning color photos and up-to-date range maps--contributors highlight key ecological roles that lagomorphs play and explain in depth how scientists around the globe are working to save vulnerable populations. Thematic introductory chapters cover a broad spectrum of information about pikas, rabbits, and hares, from evolution, systematics, and diseases to lagomorph conservation status and management. Each animal account begins with the complete scientific and common names for each species. A description of the appearance and unique morphological characteristics is accompanied by a range of standard measurements of adult specimens. Subsequent sections discuss known paleontological data concerning the species, the current state of its taxonomy and geographic variation, and various aspects of the animal's biology. Aimed at naturalists, professional biologists, and students, this book will also serve as a valuable reference for those conducting biodiversity surveys and conservation throughout the world"--